Relationship Between Perceived Community Stigma, The Quality of Mother-Child Relationship and Burnout Among Mothers of Children with Autism Spectrum Disorder Receiving Services in Private Autism Centers in Lahore, Pakistan - Waseem Hussain; Alishba Malik (Pakistan Journal of Positive Psychology, 2026)
Parents are usually the primary caregivers of children with ASD, and their care is challenging. While caring for the child with ASD, they also have to deal with stigma and incorrect perceptions from society, which may cause them to become exhausted and impact their relationship with their child. The purpose of the current research was to investigate relations between parents' perceived community stigma, the quality of mother child relationship and burnout among mothers of children with autism spectrum disorder receiving services in private autism centers in Lahore, Pakistan. It used a quantitative correlational research method to investigate correlations. Sample of 300 mothers of children with ASD were drawn through convenience sampling method from private autism centers of Lahore. The mothers completed provided demographic information form, Parent Perceptions of Community ASD Stigma Scale, The Parental Burnout Assessment and Child-Parent Relationship Scale. The data were analyzed through SPSS Version 27. The analysis conducted is reliability, descriptive statistics, Pearson product moment correlation and linear regression. There was a significant negative correlation between parental burnout and parent-child relationship and between perceived stigma in the community and parent child relationship. Also, community stigma was positively correlated with parental burnout. Linear regression analyses revealed that parental burnout and perceived community stigma were predicting variables of the quality of parent child relationship. These two variables account for variation of the quality of parent child relationship. The findings indicate community stigma is connected to increased parental burnout and poorer parent child relationship. Reducing community stigma as well as providing support for parents in managing their mental health can be beneficial for improving Family functioning and parent child interactions in families of children with ASD.